The Influence Of Supervision And Competence On Employee Performance At Pt. Karya Lima Sahabat With An Organizational Climate As - Eric - Hermawan; Wahyuddin - Latunreng (International Journal of Artificial Intelligence Research, 2022)
The independent variables of supervision, competence and organizational atmosphere were used to determine the indirect effect of supervision and competence on the performance of employees of PT. Karya Lima Sahabat with an organizational atmosphere as a mediator. To determine this indirect effect, it can be done by determining the direct influence of supervision, organizational atmosphere and competence partially on the performance of employees of PT. Karya Lima Sahabat and the direct influence of supervision and competence partially on the organizational atmosphere. The method used in this study is a quantitative method with a descriptive type of research that describes the phenomenon being studied by processing 82 people who are the full sample (population) of employees of PT. Karya Lima Sahabat. To determine the direct influence of supervision, competence and organizational atmosphere on the performance of employees of PT. Karya Lima Sahabat was carried out using simple regression after the research data was tested by using validity, reliability, normality, multicollinearity and heteroscedasticity tests. Simple regression significance test can be done by t-test, by comparing tcount and ttable. The simple regression equation is significant and positive if tcount > ttable. The direct influence of supervision, competence and organizational atmosphere was simultaneously carried out with multiple regression. The significance test was carried out with the F-test. The multiple regression equation is significant and positive if Fcount > Ftable. The results of the study found that all effects, both direct and indirect, were significant and positive. The influence of supervision, competence and organizational atmosphere partially in percent on the performance of employees of PT. Karya Lima Sahabat in percent were 23.3%, 27.0% and 27.3%. The effect of supervision and competence in percent partially on organizational atmosphere is 26.3% and 44.7%. The direct influence of supervision, competence and organizational atmosphere simultaneously on the performance of employees of PT. Karya Lima Sahabat in percent is 33.1%.